Editor's choice - association between peri-operative aspirin resistance and cardiovascular outcome (POPART-CVO): a prospective non-interventional cohort study - Dehne, Sarah; Heck, Christian; Sander, Julia; Meisenbacher, Katrin; Arens, Christoph; Niklas, Christian; Kronsteiner, Dorothea; Giannitsis, Evangelos; Böckler, Dittmar; Weigand, Markus A.; Larmann, Jan (European journal of vascular and endovascular surgery, 2022)
Objective - New onset aspirin resistance during surgery, known as peri-operative aspirin resistance, is observed in up to 30% of vascular surgery patients and is associated with post-operative myocardial damage; questioning aspirin effectiveness towards peri-operative cardiovascular events. The objective of this study was to prospectively evaluate whether peri-operative aspirin resistance in vascular surgery is associated with an adverse cardiovascular outcome. - Methods - Based on a sample size calculation, 194 adult elective vascular or endovascular surgery patients receiving aspirin were analysed in this prospective, single centred, non-interventional cohort study. Platelet function was measured before surgery, one hour after incision, four hours post-operatively, and on the morning of the first and second post-operative days using the Multiplate analyser. The primary outcome was myocardial injury after non-cardiac surgery (MINS). Secondary outcomes included major bleeding, admission to intensive care unit, length of hospital stay, and major adverse cardiac and cerebrovascular events. Subgroup analyses were performed for patients with different cardiovascular risk and for patients who underwent endovascular surgery. - Results - Peri-operative aspirin resistance was observed in 27.8% of patients but was not associated with MINS (27.8% vs. 32.1%, aspirin resistance vs. no aspirin resistance, OR 0.812, 95% CI 0.406 - 1.624, p = .56) or with any of the secondary endpoints (all p > .050). In nine of the 10 subgroup analyses, aspirin resistance was not associated with a difference in MINS rate. However, in patients with a low cardiovascular risk profile (RCRI 0-2), MINS occurred more frequently in patients without aspirin resistance (p = .049). - Conclusion - This study confirmed previous reports demonstrating that peri-operative aspirin resistance is common in patients undergoing vascular or endovascular surgery. However, in patients who continue aspirin throughout the peri-operative period, aspirin resistance is a phenomenon, which does not appear to be related to MINS. Measuring peri-operative platelet function using the Multiplate analyser with the intention to identify and potentially prevent or treat peri-operative aspirin resistance seems to be dispensable.